Saturated fatty acids modulate cell response to DNA damage: implication for their role in tumorigenesis. - Li Zeng (Public Library of Science (PLoS), 2008)
DNA damage triggers a network of signaling events that leads to cell cycle arrest or apoptosis. This DNA damage response acts as a mechanism to prevent cancer development. It has been reported that fatty acids (FAs) synthesis is increased in many human tumors while inhibition of fatty acid synthase (FASN) could suppress tumor growth. Here we report that saturated fatty acids (SFAs) play a negative role in DNA damage response. Palmitic acid, as well as stearic acid and myristic acid, compromised the induction of p21 and Bax expression in response to double stranded breaks and ssDNA, while inhibition or knockdown of FASN enhanced these cellular events. SFAs appeared to regulate p21 and Bax expression via Atr-p53 dependent and independent pathways. These effects were only observed in primary mouse embryonic fibroblasts and osteoblasts, but not in immortalized murine NIH3T3, or transformed HCT116 and MCF-7 cell lines. Accordingly, SFAs showed some positive effects on proliferation of MEFs in response to DNA damage. These results suggest that SFAs, by negatively regulating the DNA damage response pathway, might promote cell transformation, and that increased synthesis of SFAs in precancer/cancer cells might contribute to tumor progression and drug resistance.